The Training on saintific learning design with optimizing intelligence and student learning style in Ar-Royan Natural School Padang - yerizon yerizon; Atus Amadi Putra; Helma Helma (Fakultas MIPA Universitas Negeri Padang, 2019)
The problem faced by partners is the teacher's inability to design curriculum learning 2013 by paying attention to students' intelligence such as interpersonal, intrapersonal, visual, and kinesthetic. Students in a class have a variety of intelligence and learning styles. Teachers should accommodate all these intelligences in the learning process. It requires an activity on how to design 2013 curriculum learning planning. The method used in this training activity consists of three parts, namely the presentation of theories about designing curriculum learning 2013. In this activity questionnaire sheets were used. The questions are arranged to see the results of the implementation of the design of planning the 2013 curriculum learning activities with attention to student intelligence. The training activities carried out are able to improve teacher competence (teacher understanding and skills) in designing and making media that is appropriate to the material and intelligence and learning styles of students